Generalissimo A.V. Suvorov: General’s Persona in Memory Politics of Early 20th Century Russian Empire - A. S. Lizogub (Научный диалог)
This article addresses the utilization of heroic imagery from the past within the memory politics of the early 20th century Russian Empire. The author provides a detailed analysis of the commemoration of A.V. Suvorov’s feats during the reign of Nicholas II. It is demonstrated that the centenary of Suvorov’s death catalyzed a resurgence of interest in this heroic figure. Based on archival documents and periodical press, the study shows that efforts to immortalize the general continued after the centennial anniversary. The research establishes that Victorian themes occupied a central position in the symbolic politics of autocratic power throughout this period. The author concludes that the state actively employed the heroic image of A.V. Suvorov to legitimize the existing order and unify the empire’s populace. It is emphasized that, in the early 20th century, key instruments for shaping the memory landscape included the construction of a pantheon of national heroes, the establishment of museums, the organization of celebratory ceremonies, and the execution of educational initiatives, alongside monumental commemoration. The author asserts that narratives from military history were instrumental in creating cultural infrastructure both within and beyond the state’s borders. This article is of particular interest to researchers exploring issues related to historical memory and memory politics in the early 20th century.